GAMMA GLUTAMYL TRANSFERASE LEVELS IN PATIENTS WITH ACUTE STROKE: AN ANALYTICAL STUDY - DOONGAR SINGH; SUJATA AGARWAL; PRADEEP MITTAL; SHASHI BHUSHAN SHARMA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Stroke is a significant global health issue with a major socioeconomic burden, ranking as the second leading cause of death worldwide. While stroke rates have declined in high-income countries, they have increased in low- to middle-income countries, including India. The World Health Organization defines stroke as a disturbance of cerebral function caused by vascular factors, classified as ischemic or hemorrhagic. Methods: Ischemic stroke is primarily caused by atherosclerosis in the brain’s arteries, including the proximal aorta, leading to embolus formation. Other factors contributing to stroke include arterial stenosis, coexisting thrombosis, artery-to-artery embolism, micro atheroma, lipohyalinosis, and occlusive diseases of small brain arteries. Cardiogenic embolism, often associated with atrial fibrillation, contributes to a significant proportion of ischemic strokes. Gamma-glutamyl transferase (GGT), commonly used as a marker for alcohol consumption and liver diseases, is also linked to oxidative stress, inflammation, and atherosclerosis. Elevated GGT levels are associated with various stroke risk factors. Results: GGT plays a crucial role in cellular intake of glutathione, an important antioxidant. Paradoxically, it can generate reactive oxygen species in the presence of certain metals. Studies have found a correlation between high serum GGT levels and stroke risk, potentially due to oxidative stress and atherosclerosis progression. Conclusion: Despite its primary use as an alcohol consumption marker, GGT has emerged as a potential independent biomarker for vascular diseases, including stroke. However, limited research exists on the association between GGT and acute stroke. This study aims to evaluate GGT levels in patients with acute stroke, exploring potential differences among stroke types to better understand the impact of GGT on acute stroke.